People's Republic of China : Detailed Assessment Report on Anti-Money Laundering and Combating the Financing of Terrorism. (IMF Staff Country Reports; Country Report ;, 2019)
This report provides a summary of the anti-money laundering/combating the financing of terrorism (AML/CFT) measures in place in the People's Republic of China (China)1 as at the date of the onsite visit (July 9-27, 2018). It analyzes the level of compliance with the Financial Action Task Force (FATF) 40 Recommendations and the level of effectiveness of China's AML/CFT system and provides recommendations on how the system could be strengthened. China has undertaken a number of initiatives since 2002 that have contributed positively to its understanding of ML/TF risk, although some important gaps remain. Its framework for domestic AML/CFT cooperation and coordination is well established.